2020
DOI: 10.1007/s00204-020-02939-4
|View full text |Cite
|
Sign up to set email alerts
|

Cross-species analysis of hepatic cytochrome P450 and transport protein expression

Abstract: Most drugs and xenobiotics are metabolized in the liver. Amongst others, different cytochrome P450 (CYP) enzymes catalyze the metabolic conversion of foreign compounds, and various transport proteins are engaged in the excretion of metabolites from the hepatocytes. Inter-species and inter-individual differences in the hepatic levels and activities of drug-metabolizing enzymes and transporters result from genetic as well as from environmental factors, and play a decisive role in determining the pharmacokinetic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
46
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(48 citation statements)
references
References 56 publications
2
46
0
Order By: Relevance
“…For CYP2C, two substrates (diclofenac and diazepam) were used to cover the activities of characteristic for the most of the CYP2C forms involved. For the CYP2C38 activity, since it is similar to human CYP2C9 form [ 22 ], diclofenac was used as a substrate. The activity of CYP2C29 was determined by using diazepam as a substrate (murine CYP2C29 is homologous with human CYP2C19) [ 23 ].…”
Section: Resultsmentioning
confidence: 99%
“…For CYP2C, two substrates (diclofenac and diazepam) were used to cover the activities of characteristic for the most of the CYP2C forms involved. For the CYP2C38 activity, since it is similar to human CYP2C9 form [ 22 ], diclofenac was used as a substrate. The activity of CYP2C29 was determined by using diazepam as a substrate (murine CYP2C29 is homologous with human CYP2C19) [ 23 ].…”
Section: Resultsmentioning
confidence: 99%
“…Studies have shown a dysregulation in CYP proteins during the progression of NAFLD ( 40 ). CYP protein families are found in high concentrations in the liver and are notably responsible for drug and exogenous substrate metabolism, detoxification of environmental chemicals, bioactivation of carcinogens, and the biosynthesis of endogenous substrates ( 41 , 42 ). In addition, they play significant roles in metabolizing noncellular materials, cholesterol, vitamin D, arachidonic and retinoic acids, eicosanoids, and the biosynthesis of bile acids and steroids ( 43 ).…”
Section: Discussionmentioning
confidence: 99%
“…The effect of diabetes on the activity of CYP enzymes, particularly CYP3A, has been well established in human (Dostalek et al., 2012; Gravel et al., 2019) and animal models (Patoine et al., 2014). Nevertheless, hepatic expression of CYP2C11, the rat ortholog of human CYP2C9 (responsible for gliclazide metabolism) (Hammer et al., 2021; Pan et al., 2016) were similar between healthy Wistar and Goto‐Kakizaki rats, the latter of which represent a nonobese hereditary model for type 2 diabetes mellitus (Oh et al., 2012). This suggested a similar extent of hepatic CL of gliclazide irrespective of diabetic status.…”
Section: Discussionmentioning
confidence: 99%